The Medea of Stobaeus: a Study of a Complete Tragedy by Euripides in the Anthology (Circe de clásicos y modernos, 2025)
In this paper we aim to determine how Stobaeus reads, trims and rearranges a fully preserved tragedy –Euripides’ Medea– in his Anthology, in order to gain a better understanding of his modus compilandi. We also seek to explore how a reader of the Anthology might interpret Medea if they had access only to the fragments preserved therein. Admittedly, we do not know whether any reader of the Anthology would have been interested in such a reading, and all indications suggest they would not: more direct ways of accessing the play were available.
Keywords: Tragedy; Anthology; Medea; Euripides; Stobaeus